THE INFLUENCE OF BRAND IMAGE AND PROMOTION ON THE DECISIONS OF STUDENTS IN STIE MAHAPUTRA RIAU WITH LEARNING INTEREST AS INTERVENING VARIABLES - Deni Fajri; Teddy Chandra; Rizaldi Putra (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The purpose of this study was to determine the effect of brand image and promotion on decisions by using interest as an intervention variable. The method used in this research is the path analysis method. The sample used is 220 respondents. While the data collection by means of a questionnaire. The results showed that brand image did not have a positive and significant effect on interest. Promotion does not have a positive and significant impact on interest. Interest has a positive and significant influence on purchasing decisions. Brand image has a positive and significant influence on decisions. The promotion has a positive and significant influence on purchasing decisions. Interest is not able to mediate the effect of brand image on decisions as evidenced by the test results. Interest is not able to mediate the effect of promotion on decisions as evidenced by the test results.